Strategi Pengamanan Cyber: Lingkup Kerjasama dalam Menghadapi Ancaman Cyber - Chintya Pradilla Putri; Widya Anggraini; Yuda Mahendra Hasibuan; Nurbaiti, Nurbaiti (Yayasan Literasi Sains Indonesia, 2023)
Threats to the security of important objects and files are growing rapidly. In the rapid development of the digital era, the security of goods and files has become very important, which is a big problem in terms of cyber security. Cybercriminals are more clever and skilled at exploiting information security gaps in digital systems. Improving cyber security requires a thorough analysis of the threats faced in the digital environment and the solutions that can be implemented. The aim of this research is to analyze the main targets, identify the main challenges to protect them from cyber attacks, evaluate and recommend measures and strategies to improve file security, explore case studies related to threats and solutions in the digital environment. The qualitative approach uses data collection methods. Potential threats of cyber crime in Indonesia include hacking, cracking, cyber sabotage and spyware. The risk management process includes identification, evaluation, handling and controlling risks. To anticipate danger, therefore, technology experts are needed to support the development of defense systems in developed countries and establish a cyber security command center.